2016
DOI: 10.4314/njp.v43i1.9
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of liver diseases among children attending the National Hospital Abuja, Nigeria

Abstract: Background: Diseases of the liver contribute to childhood morbidities and mortality. Early recognition and proper management of liver diseases can limit the progression to irreparable damage which requires liver transplant. However, there is scarcity of data in the pattern of liver disease in Nigerian children. Objective: To describe the pattern of paediatric liver diseases among children seen at the National Hospital, Abuja. Methods: A retrospective, descriptive study conducted at the Paediatric Gastroenterol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…The most common sign noted was icterus (51.1%), hepatomegaly (42%), followed by ascitis and splenomegaly (26.6%) each. Similarly, a study done in Nigeria has shown jaundice (71.4%), abdomen pain (40.5%) as the most common symptoms and jaundice (71.4%) , hepatomegaly (38.1%), splenomegaly (19%) as the most common signs [2].…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…The most common sign noted was icterus (51.1%), hepatomegaly (42%), followed by ascitis and splenomegaly (26.6%) each. Similarly, a study done in Nigeria has shown jaundice (71.4%), abdomen pain (40.5%) as the most common symptoms and jaundice (71.4%) , hepatomegaly (38.1%), splenomegaly (19%) as the most common signs [2].…”
Section: Discussionmentioning
confidence: 78%
“…The outlook of hepatobiliary disorders has undergone tremendous change with advent of better diagnostic tools like ultrasound, radionuclear scan, viral and autoimmune markers, endoscopic retrograde cholangiography, digital substraction angiography and improved sectioning and staining techniques of liver tissue specimens [1]. Diseases of the liver contribute [2]. Liver diseases among children include a broad spectrum of disorders such as infections, developmental abnormalities and metabolic disorders that finally result in hepatic dysfunction and cirrhosis.…”
Section: Introductionmentioning
confidence: 99%
“…However, hepatitis C infection was the cause of CLD in 31.66% of children in the Tahir et al (19) investigation. And in a research from Nigeria by Ahmed et al [20], 57.1 percent of the children tested with viral aetiology were CLDs. There have been 21.4 percent non-infectious instances of bile atresia, cholestatic hepatitis, hepatoblastoma and galactosaemia.…”
Section: Discussionmentioning
confidence: 95%
“…This case-control study was carried out on 60 children who attended the outpatient hepatology clinic at Benha university hospitals and National liver institute, Menoufia University after informed written consent was obtained from the parents or caregivers of enrolled children after explanation of the study, the laboratory work was done in clinical pathology department, Benha University. 20…”
Section: Methodsmentioning
confidence: 99%
“…8 In our study 70% of the children were five years of age or older (59/84) compared to study from Nigeria showing 62% of the children in this age group. 9 The differences in mean age, gender distribution and age distribution reflect <0.001 Table-III the regional population differences of these countries. Chronic liver disease comprised 58.3% (49/84) of the cases followed by 34.5% (29/84) of the cases with acute hepatitis in our cohort.…”
Section: Discussionmentioning
confidence: 96%